Factors affecting stress in anode particles during charging process of lithium ion battery. (November 2021) - Wang, Yanan; Li, Hua; Wang, Zhengkun; Lian, Chen; Xie, Zongfa
Highlights: An electrochemical and mechanical coupling model of a LIB with the NMC cathode and graphite anode is built at mesoscopic scale. The maximum stress in the anode particles at the end of charging increases with the charging rate and electrode thickness. The maximum stress in the anode particles at the end of charging decreases with the spacing coefficient and diffusion coefficient. The conclusion could be referenced in the microstructure design of the anode electrode from the perspective of mechanical safety. Abstract: During charging and discharging, the insertion and extraction of lithium ions into and from the active materials can cause stress in a lithium ion battery (LIB). Excessive stress will lead to cracking, breaking and pulverization of active particles, which can result in multiple failure modes such as capacity decay and life reduction of the battery. In this research, an electrochemical and mechanical coupling model of a LIB with the NCM cathode and graphite anode is built at mesoscopic scale. The electrochemical and mechanical characteristics of the model during the charging process are analyzed. By changing the charging rates and design parameters of the anode electrode such as the particle radius, spacing coefficient, electrode thickness and diffusion coefficient, the effects of them on the lithium concentration, strain and stress in the anode particles during the charging process are investigated. The results show that lower charging rate, greater spacing coefficient, smaller electrode thickness and greater diffusion coefficient could help to decrease the stress in anode particles during charging.